Ethical Perceptions of Expatriate and Local Managers in Hong Kong - McDonald, Gael M. (Journal of business ethics, 1997)
In an effort to build on the current knowledge of ethical behaviour in Asia this paper proposes to replicate existing ethical research and to investigate specific questions relating to intra-cultural differences in Hong Kong. Four major conclusions were derived from this descriptive empirical study. A statistically significant correlation exists between age and ethical beliefs, with older employees less likely to express agreement to an unethical action than younger employees. In contrast to many previous studies no statistically significant differences in ethical beliefs were found in relation to gender, level in the organisation, company size, and whether the respondent worked in a multinational or local company. Significant differences in responses to ethical dilemmas were identified between local and expatriate personnel with expatriate respondents indicating a lower level of agreement to unethical actions. For local respondents, of Hong Kong origin, there was no significant correlation between level of education, religiosity, years of business experience, functional origin and their ethical responses.